Relaciones interpersonales y clima laboral en Empresa Minera J&S Contratistas Generales S.A.C., provincia de Pataz: 2020 - Avalos Ibañez, Amy Rossy (2022)
This thesis was carried out in order to explain the influence of interpersonal relationships on the work environment in the Mining Contractor Company J&S Contractors General S.A.C., Pataz province: 2020. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 183 workers, with whom we worked applying the methods and techniques of quantitative research (Statistical method and as a technique to the survey) and the qualitative research (inductive - deductive method; and direct observation and interview as techniques). Determine interpersonal relationships and their relationship with the work environment of the staff, based on the dimensions of the relationships between workers (poor communication, lack of leadership, poor teamwork). The dimensions of the dependent variable are also, (distrust, internal conflicts and job dissatisfaction). In conclusion, poor interpersonal relationships directly influence the work environment of the staff, where it allows them to function in an unpleasant and dissatisfied environment due to the results not achieved in the execution of their responsibilities and duties that they want to fulfill daily in this mining company. Finally, we consider that the organization should implement training programs to implement a motivational plan, promote transformational leadership and work as a team to improve the level of production and productivity of the business organization.